IMPLEMENTATION OF MORAL EDUCATION IN SCHOOLS TO FACE THE DEVELOPMENT OF SCIENCE AND TECHNOLOGY AS A FORTRESS OF DEMORALIZATION - Waziana, Winia; Saputra, Ricco Herdiyan; Sinthiya, Ida Ayu Putu Anggie (JLCEdu (Journal of Learning and Character Education), 2021)
The phenomenon of moral decline has colored the education world. Several students and education graduates show an attitude that is not commendable. Many students and college students are involved in brawls, criminal acts, theft, muggings, sexual deviations, involved in drugs, bullying, and other criminal acts. Even among students, brawls often occur. Demonstrations that protest against policies do not only occur on campuses but also occur among high school students and even elementary school students, which sometimes end in violence. This disgraceful act has disturbed the community. the study will describe how important value education is to improve the morality of students in high school, and will also discuss the causes that might trigger a moral crisis in students, as well as what steps should be taken to rebuild morale. The research is a qualitative study. It includes the process of exploring and understanding the meaning of individual and group behavior, describing social problems or humanitarian problems. The resulting state that moral education is something that must be given to students in schools, from elementary schools to tertiary institutions. Because moral education can shape a person's personality so that he becomes a good human being, a citizen, and a good citizen by the mandate contained in the functions and objectives of national education in the Law on the National Education System. The role of teachers and learning designers in developing moral learning strategies in schools should provide more opportunities for students to take moral roles, both within the family environment, school environment, peer environment, and the wider community environment by providing an example through the process of imitation